On-chip coherent photonic-phononic memory - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (Proceedings - International Conference Laser Optics 2018, ICLO 2018, 2018)
We store optical data in acoustic waves on a planar waveguide based on stimulated Brillouin scattering (SBS) and demonstrate multiple conversions of information between the optical and acoustic domain. We show the coherent acousto-optic transfer by retrieving multiple amplitude and phase levels with GHz bandwidth and demonstrate multi-wavelength operation.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Nonlinear optics; Photonic integrated circuits; Stimulated Brillouin scattering